Silly citizenship - Hartley, John (Routledge, 2010)
This paper traces historical changes in the concept of citizenship, in order to show how it has shifted from a state enterprise to a form of self-organising, user-created, ludic association, modelled by online social networks in which children - formally non-citizens but crucial to the continuing and changing discursive practices of citizenship-formation - are active agents. The implications of 'silly' citizenship for communication scholarship are considered. © 2010 Taylor & Francis.